Salads for all seasons - Waugh, Mary Lana (My University, 1899)
Introduction: Webster calls a salad “a preparation of uncooked herbs, usually dressed with salt vinegar, oil or spices, and eaten for giving a relish to other food, “ a dish composed of some kinds of meat, especially of chicken or lobster, chopped fine and mixed with uncooked herbs, as lettuce, and seasoned with condiments.” The standard dictionary calls it a dish of green herbs or vegetables, usually uncooked and chopped fine or sliced, mixed with cold chopped cooked meats and served with a dressing in which oil and vinegar play a prominent part. As we speak of salad ordinarily, it may refer to fruits, meats, nuts or vegetables, or some combination, chopped fine and served cold with some kind of salad dressing.
Citation: Waugh, Mary Lana. Salads for all seasons. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Prepartion of Salad; Food Value; Types of Salads; Theses; Manuscripts (documents)